Children's songs in the development of oral expression in children at the initial level. Private educational institution “Virgen de Copacabana”. Puente Piedra. Lima - Huisa Sulca , Ana María (2024)
This scientific study entitled Children's songs in the development of oral expression in children of the initial level. Private educational institution "Virgen de Copacabana". Puente Piedra. Lima, its objective was to establish whether the children's song strategy improves oral expressions. A research with a quantitative, transversal approach and quasi-experimental design. We used a 15-item instrument validated by 3 experts and the Student t statistician to measure the results. We worked with 20 students of 5 years for both the experimental sample and the control sample. In the workshop, three dimensions were worked on: Vocalization, pronunciation and coherence, oral expression was evaluated. The existence of a significant difference is concluded when applying the statistical test whose results are: t: p <5.187 They lead us to affirm that there is a significant difference between the experimental group and the control group, it is demonstrated that effectively children's songs significantly influence the oral expression of the significant study sample in the improvement of their oral expression.